Mono‐ and digalactosyldiacylglycerol composition of the marennine‐producing diatom, Haslea ostrearia: Comparison to a selection of pennate and centric diatoms. Issue 3 (21st May 2013) - Dodson, V. Joshua; Dahmen, Jeremy L.; Mouget, Jean‐Luc; Leblond, Jeffrey D.
Summary: Diatoms are one of the largest groups of primary producers in the oceans, yet despite their environmental importance little is known about their plastidial lipid biochemistry. It has been previously reported that Skeletonema species contain primarily C16 /C16 and C20 /C16 forms of mono‐ and digalactosyldiacylglycerol (MGDG and DGDG, respectively). Likewise, it was also reported that Phaeodactylum tricornutum contains primarily C16 /C16 and C20 /C20 forms of MGDG and DGDG. We seek to relate their studies to other diatoms, both in the centrics and pennates, with particular focus on the marennine‐producing pennate diatom, Haslea ostrearia . To this end, the composition and positional distribution of fatty acids of MGDG and DGDG were examined using positive‐ion electrospray ionization/mass spectrometry (ESI/MS). Two centric diatoms, Skeletonema marinoi and Thalassiosira weissflogii, and the pennate diatom, P. tricornutum, contained primarily C20 /C16 ( sn ‐1/ sn ‐2) and C18 /C16 forms of MGDG and DGDG. The other pennate diatoms, H. ostrearia and Navicula perminuta, contained primarily C18 /C16 or C18 /C18 forms of MGDG and DGDG, indicating a previously unrecognized fatty acid diversity in diatom MGDG and DGDG.